A CRITICAL DISCOURSE ANALYSIS OF THREE (3) ADVERTISEMENT ENTITLED “ALWAYS ON, BEBAS ITU NYATA” GIRL’S VERSION - PRAWITASARI, REGINA WIKAN PANGREPTI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Critical Discourse Analysis (CDA), Advertisement, Text Analysis, Three (3). This study is conducted to know the power of Three (3) advertisement’s narration entitled “Always On, Bebas itu nyata” towards the society. Since, this advertisement touches the Indonesian culture which gives the impact towards  the society. There are two problems to be solved, namely: (1)What is the meaning of each utterances in the Three (3) advertisement “Always On, Bebas itu nyata” girl version based on Fairclough’s three dimension model of CDA?; (2) What are society interpretations on the depiction of freedom on Three (3) advertisement “Always On, Bebas itu nyata”?.This study employs qualitative approach by using content or document analysis. Document analysis is applied because the aim of this study is to describe the meaning on Three (3) advertisement’s utterances narration and the society’s interpretation. The data of this research were all utterances found in Three (3) entitled “Always On, Bebas itu nyata” (girl’s version) and the comment from internet regarding this advertisement. The writer applied several processes in collecting the data in certain order as follow: (1) downloading the complete video entitled “Always On, Bebas itu nyata” girl’s version from Youtube,  (2) transcribing the utterances by playing and pausing the video, (3) reading the whole transription of the utterances in order to check the utterances for understanding the message of advertisement, and (4) finding the society’s comments in the Youtube’s comment box and from the personal blogs.This present study reveals that based on society interpretation on the Three (3) advertisement narration, the society tends to see and directly related this advertisement’s narration with the norm and culture in Indonesia without thinking about the main purpose of the advertisement maker.Finally, the writer suggests that the next researcher enrich the field of this study and possibly explore other numerous object with different theory of CDA. It will be very useful for the knowledge development especially in critical discourse analysis.